2021
DOI: 10.3390/met11101583
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Process Conditions for Additive Manufacturing Technology Combining High-Power Diode Laser and Hot Wire

Abstract: A high-efficiency additive manufacturing technology that combines a high-power diode laser with a large-rectangle spot (beam width of 11 mm) and a hot-wire system was developed. The hot-wire system can generate Jo ule heat by wire current and heat a filler to its melting point independently from the main heat source of a high-power diode laser. A simple calculation method to derive the appropriate hot-wire current of Z3321-YS308L was proposed with verification by hot-wire feeding experiments without laser irra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Liu et al reported the same instabilities as Zhu et al [108] in preheating with different voltages by noting that at a high voltage, arcing occurred, and large spatters were generated [191,192]. They also compared the influence of increasing laser power and preheating voltage on the process stability and geometrical appearance of the beads.…”
Section: Figure 28mentioning
confidence: 78%
See 4 more Smart Citations
“…Liu et al reported the same instabilities as Zhu et al [108] in preheating with different voltages by noting that at a high voltage, arcing occurred, and large spatters were generated [191,192]. They also compared the influence of increasing laser power and preheating voltage on the process stability and geometrical appearance of the beads.…”
Section: Figure 28mentioning
confidence: 78%
“…Similarly, Huang et al [47] confirmed the height increase with an increase in WFS in aluminum alloy. However, an increased mass of wire resulted in an augmented melt pool volume per unit length and, consequently, increased bead width [108]. Such deviations exist in the literature when utilizing various materials with increasing WFS.…”
Section: Bead Geometrymentioning
confidence: 99%
See 3 more Smart Citations